Resection of Ependymomas Infiltrating the Fourth Ventricular Floor: Anatomosurgical and Stimulation Mapping Techniques. Issue 5 (22nd May 2022) - Sharma, Priya; Sefcikova, Viktoria; Sanders, Brett; Soumpasis, Christos; Waraich, Manni; Samandouras, George
Abstract : BACKGROUND: Despite the importance of complete, gross total resection (GTR) of fourth ventricular ependymomas, significant morbidity and/or subtotal resections are reported, particularly when the ventricular floor is infiltrated. Step-by-step technique descriptions are lacking in the literature. OBJECTIVE: To describe monitoring and stimulation mapping techniques and surgical nuances in the challenging subgroup of infiltrating fourth ventricular ependymomas by a highly illustrated, step-by-step description. Superimposed outlines of cranial nerve nuclei on the surgical field demonstrate critical anatomy and facilitate understanding in a way not previously presented. METHODS: We reviewed the microanatomical and neurophysiological prerequisites of resecting a diffusively infiltrating fourth ventricular ependymoma. RESULTS: We achieved GTR with the use of reproducible stimulating mapping and accurate cranial nerve nuclei identification. CONCLUSION: Enhanced microanatomical understanding, reproducible stimulation mapping, and meticulous resection techniques can result in GTR, even in diffusively infiltrating ependymomas.